Forming innovative work behavior prospective police investigator through self-efficacy and job crafting in the post-COVID-19 - Girindra Wardana Akbar Ramadhani; Fendy Suhariadi; Bagong Suyanto; Ian Firstian Aldhi; Elisabeth Supriharyanti; Dwi Hardaningtyas; Ansar Abbas (Discover Sustainability)
Abstract This study investigates the relationship between self-efficacy, job crafting, and innovative work behavior in Indonesian prospective police investigators. The research, conducted at the National Police Education and Training Institute, utilized a quantitative approach, gathering data from 448 participants via a structured online questionnaire employing a five-point Likert scale. The analysis was conducted using SmartPLS4. The findings indicate that self-efficacy does not directly affect innovative work behavior. However, job crafting serves as a complete mediator in this relationship, underscoring its essential role in promoting innovation within organized professional environments. This study enhances the current body of literature by applying Bandura’s Social Cognitive Theory to law enforcement settings, highlighting the intricate interplay among cognitive, behavioral, and environmental elements. Incorporating job crafting-focused training in police education is recommended to improve adaptability and innovation, thereby addressing the operational challenges faced by law enforcement in the post-pandemic context. Future research should investigate these dynamics across various cultural and organizational contexts to further validate the findings and examine longitudinal changes throughout an officer’s career.